Correction: Citrate combustion synthesized Al-doped CaCu3Ti4O12 quadruple perovskite: synthesis, characterization and multifunctional properties. Issue 30 (24th July 2020) - Pal, Kamalesh; Dey, Arka; Jana, Rajkumar; Ray, Partha P.; Bera, Parthasarathi; Kumar, Lalit; Mandal, Tapas Kumar; Mohanty, Paritosh; Seikh, Md. Motin; Gayen, Arup
Abstract : Correction for 'Citrate combustion synthesized Al-doped CaCu3 Ti4 O12 quadruple perovskite: synthesis, characterization and multifunctional properties' by Kamalesh Pal et al., Phys. Chem. Chem. Phys., 2020, 22, 3499–3511, DOI: ; 10.1039/C9CP05005A .